Energy Aspects of Flavonoid Extraction from Rowanberry Fruits Using Pulsed Ultrasound-Assisted Extraction - Zbigniew Kobus; Monika Krzywicka (Energies, 2023)
The aim of the study was to analyze the influence of the dimensions of extraction cells on the energy aspects and extraction efficiency of flavonoids from rowanberry fruits (S. aucuparia L.). The total flavonoid content was determined using the spectrophotometric method. Response surface methodology (RSM) was used to optimize the variables under investigation. The flavonoid content in the obtained extracts ranged from 0.17 to 0.66 mg QE/g dry matter for cells with a diameter of 3.5 cm, and from 0.19 to 0.7 mg QE/g dry matter for cells with a diameter of 2.5 cm, depending on the other experimental conditions. The energy consumption during extraction in the 3.5 cm diameter cell ranged from 0.451 kJ to 26.120 kJ, while for the 2.5 cm diameter cell, it ranged from 0.637 kJ to 25.677 kJ. The unit energy consumption for the 3.5 cm diameter cell ranged from 1.47 kJ/mg QE/g to 48.92 kJ/mg QE/g. For the 2.5 cm diameter cell, these values ranged from 2.17 kJ/mg QE/g to 40.64 kJ/mg QE/g. Significant effects of the dimensions of the extraction cells on flavonoid yield and unit energy consumption were observed, while there was no impact on electricity consumption. The dimensions of the extraction cells were also found to influence the form of the obtained empirical models.